Introduction I-CASE-Technology into Application Development - Experiences and Learning from Projects in an Educational Environment - Eicker, Stefan; Kurbel, Karl (Proceedings of the 3rd European Conference on Information Systems (ECIS '95), 1995)
1-CASE (Integrat;d CASE) promises significant productivity gains, but successful use requires profound knowledge ofmethodology and tools. Since both methodology and toolsets are rather complex, it takes time and e:1..-perience to acquire that knowledge. In this paper, we report about our experience with introduction of a comprehensive 1-CASE toolset (ADW) into university education. The process covered two years, starting with tool evaluation and exploration, and first use of tools in courses on IS development, before a pilot project and subsequently a three-person-year productive project were carried out. Tue latter project ended successfully witb code generatiO,n (338,000 lines of code). Tue paper focusses on the learning process the teaching staff·went through. Some insights gained will also hold for industrial 1- CASE use.